Are airline workers planning career turnover in a post-COVID-19 world? Assessing the impact of risk perception about virus infection and job instability. (September 2021) - Han, Heesup; Koo, Bonhak; Ariza-Montes, Antonio; Lee, Youngseok; Kim, Hye-Ran
Abstract: Airline workers have been suffering risks of job instability and virus infection since the outbreak of COVID-19. This research developed a novel framework explicating airline workers' career turnover decision formation by considering the influence of perceived risks of virus infection and job instability during the COVID-19. A quantitative approach using a survey method was utilized to attain research goals. Our empirical findings revealed that airline image, attitude, and commitment have a significant influence on employee career turnover intention. Both attitude and commitment were identified as essential mediators. In addition, perceived risks of virus infection and job instability significantly moderated the relationships among attitude, commitment, and employee career turnover intention. The effectiveness of the proposed theoretical framework for career turnover intention was demonstrated. Our findings help researchers and entrepreneurs find effectual ways to lower competent workers' career turnover and raise their approach behaviors in a post-COVID-19 world.